Centrifugally-Spun Carbon Microfibers and Porous Carbon Microfibers as Anode Materials for Sodium-Ion Batteries - Dirican, Mahmut; Zhang, Xiangwu (Elsevier Science Bv, 2016)
Natural abundance and low cost of sodium resources bring forward the sodium-ion batteries as a promising alternative to widely-used lithium-ion batteries. However, insufficient energy density and low cycling stability of current sodium-ion batteries hinder their practical use for next-generation smart power grid and stationary storage applications. Electrospun carbon microfibers have recently been introduced as a high-performance anode material for sodium-ion batteries. However, electrospinning is not feasible for mass production of carbon microfibers due to its complex processing condition, low production rate and high cost. Herein, we report centrifugal spinning, a high-rate and low-cost micro fiber production method, as an alternative approach to electrospinning for carbon microfiber production and introduce centrifugally-spun carbon microfibers (CMFs) and porous carbon microfibers (PCMFs) as anode materials for sodium-ion batteries. Electrochemical performance results indicated that the highly porous nature of centrifugally-spun PCMFs led to increased Na+ storage capacity and improved cycling stability. The reversible capacity of centrifugally-spun PCMF anodes at the 200th cycle was 242 mAh g(-1) which was much higher than that of centrifugally-spun CMFs (143 mAh g(-1)). The capacity retention and coulombic efficiency of the centrifugally-spun PCMF anodes were 89.0% and 99.9%, respectively, even at the 200th cycle. (C) 2016 Elsevier B.V. All rights reserved.
Zhang, Xiangwu/0000-0002-6236-6281; Dirican, Mahmut/0000-0002-2559-6467
Keywords: Sodium-Ion Battery; Centrifugal Spinning; Porous Carbon Microfibers; Capacity Retention; Coulombic Efficiency